Conservative Treatment of Ewing’s Sarcoma of the Uterus in Young Women - Giuseppe Loverro; Leonardo Resta; Edoardo Di Naro; Anna Maria Caringella; Salvatore Andrea Mastrolia; Mario Vicino; Massimo Tartagni; Luca Maria Schonauer (Case Reports in Obstetrics and Gynecology)
Ewing sarcoma-primitive neuroectodermal tumors (ES/PNETs) constitute a family of neoplasms characterized by a continuum of neuroectodermal differentiations. ES/PNET of the uterus is rare. There are 48 cases of ES/PNET of the uterus published in the literature as far as we know. We describe a case of Ewing sarcoma of the uterus occurring in a 17-year-old woman presenting with a two-month history of pelvic pain. After surgical excision and microscopic, immunohistochemical, and electron microscopy examination, the diagnosis of Ewing sarcoma of the uterus was suggested. This report will discuss the diagnosis and surgical and clinical management of Ewing uterine sarcoma in young women, according to the available literature. In spite of the rarity of ES/PNETs, they should be taken into account in the differential diagnosis of uterine neoplasms in young women.